Using Wattpad as a Media to Foster Better Literacy Skills: Extensive Reading and Creative Writing - Widiasmara, I Komang (Journal of Linguistics, Literacy, and Pedagogy, 2023)
Numerous digital platforms have been invented to provide flexible and joyful learning process. For instance, online learning platforms enable students to read and write related to their passion. In providing digital literacy for learning, one of the most valuable platforms can be used is Wattpad, an online reading and writing platform with various genres. Wattpad offers free features to have extensive reading and creative writing. This platform is an effective media to foster students’ reading interest and emerge students to express creativities in writing. This study attempted to investigate the effectiveness of digital platform Wattpad as a learning media to foster literacy skills such as reading and writing. The research used descriptive qualitative method and the data were collected by library research which reviewed related studies about Wattpad. Based on several studies reviewed, it was found that there is a positive feedback of using Wattpad as a learning media to improve literature skills. Those empirical studies revealed that by using Wattpad students can improve their learning habits in terms of reading and writing. Therefore, Wattpad is an alternative media to provide an enjoyable learning experience which has purposes for any aspects such as for career, education, learning, creativity and entertainment.